Analysis of Mangrove Density using NDVI and Macrobenthos Diversity in Ampekale Tourism Village South Sulawesi, Indonesia - Arfan, Amal; Maru, Rosmini; Nyompa, Sukri; Sukri, Irwansyah; Juanda, Muhammad Faisal (Jurnal Sylva Lestari, 2024)
The mangrove ecosystem faces significant challenges, as its quality and quantity are threatened with decline. This study aimed to analyze the mangrove density and macrobenthos diversity in the Ampekale Ecotourism Village, Indonesia. This research utilizes remote sensing image analysis through the Normalized Difference Vegetation Index (NDVI) method. Complementary ground-check surveys were conducted to ascertain the density and diversity of mangrove and macrobenthos species. The overall mangrove density in the Ampekale area was relatively high, with some areas displaying moderate density. The sequence of mangrove species, from most common to least common, includes Rhizophora mucronata, Avicennia marina, Avicennia alba, Rhizophora apiculata, Sonneratia alba, Bruguiera gymnorhiza, and Acanthus ilicifolius. The most prevalent macrobenthos belong to the Crustacea class, such as Uca sp., Sesarma, Metaplax sp., and Scylla serrata. Moreover, the most diverse macrobenthos belong to the Gastropods class. The distribution of this biodiversity depends on their location (coastal or inland), tidal fluctuations, and river estuaries. Mangrove ecosystems situated in estuaries with high densities exhibited elevated macrobenthos abundance. This correlation suggests that areas characterized by dense mangroves also harbor stable ecosystem conditions with abundant macrobenthos. In contrast, ecosystems featuring lower biodiversity demonstrated reduced stability. These findings contribute valuable insights into the conservation and sustainability of mangrove ecosystems. Keywords: ecotourism, macrobenthos, mangrove density, mangrove ecosystem, NDVI